Response surface method-driven design of experiments for the synthesis of fly ash-based geopolymers in the gallic acid optimized removal from wastewater - Ana Paula Ferreira; Ana Paula S. Natal; Arthur P. Baldo; Adriano S. Silva; Jose L. Diaz de Tuesta; Pricila Marin; José A. Peres; Helder T. Gomes (Chemical Engineering Journal Advances)
The growing need for sustainable wastewater treatment solutions has led to exploring alternative materials to explore large-scale and reliable technologies. This study focuses on optimizing the synthesis of geopolymers based on fly ash using a Box-Behnken experimental design to enhance their adsorption efficiency for phenolic compounds, as gallic acid model pollutant which are widely found in wastewater leaching from landfills. Fifteen geopolymer samples were synthesized, characterized, and tested for adsorption performance. Various techniques were employed, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy. The optimization process highlighted the significance of the Si/Al mass ratio, NaOH molar concentration, and Na₂SiO₃/NaOH as variables in the geopolymers production. Geopolymer samples demonstrated significant adsorption capacities, with GP_2.0_10_2.5 achieving a maximum adsorption capacity of 75.8 mg g-1. Kinetic studies indicated that the pseudo-first-order model best described the adsorption process. At the same time, equilibrium data fitted well with both Langmuir and Freundlich isotherms, with GP_2.0_10_2.5 showing the best fit for the Langmuir model. These findings reveal the potential of geopolymers derived from fly ash as cost-effective adsorbents in wastewater treatment, promoting the reuse of industrial waste within the framework of a Circular Economy.